KARAKTERISASI DIFFRAKSI SINAR-X (XRD) MATERIAL FERROELEKTRIK BARIUM TITANAT (BaTiO3) - Rahmi Dewi; Krisman '; Usman Malik; Fauzan ' (Komunikasi Fisika Indonesia, 2014)
Ferroelectric material Barium Titanat (BaTiO3) has been made with the comparison of 1:1from chemical reactionof Barium Carbonat (BaCO3) and Oxide Titanium (TiO2). The sample at pra-sinter at temperature of 400oC and printed in the form of pellets.The pellet were anneled with the temperature of 700oCand then characterized using XRD. The results of characterization using XRD was described on a graph between the intensity versus 2 theta angle. TheXRDresultsBaTiO3 before annelingdoes not show any peaks, this mean that the structure of BaTiO3before annelingis amorfus structure. The XRDresult BaTiO3 after annelingshowedsome peaks, the positions of the peaks on 2θ are 23.32°, 32.72°, 38.40o, 45.52o, 52.04°, 57.80o. After anneling, the peaks become wider, this mean the samples become crystaline in structure. At standard temperature (0oC to 320oC) the samples of BaTiO3 has tetragonal formbut on the temperature 700oC after being anneledit changed into Cubic.